Organized Crime Business Activities and Their Implications for Law Enforcement, 1986-1987 - Edelhertz, Herbert ([Verlag nicht ermittelbar], 1991)
This project was undertaken to investigate organized criminal groups and the types of business activities in which they engage. The focus (unit of analysis) was on the organized groups rather than their individual members. The project assessed the needs of these groups in pursuing their goals and considered the operations used to implement or carry out their activities. The data collected address some of the following issues: (1) Are business operations (including daily operations, acquiring ownership, and structuring the organization) of organized criminal groups conducted in a manner paralleling legitimate business ventures? (2) Should investigating and prosecuting white-collar crime be a central way of proceeding against organized criminal groups? (3) What are the characteristics of the illegal activities of organized criminal groups? (4) In what ways are legal activities used by organized criminal groups to pursue income from illegal activities? (5) What is the purpose of involvement in legal activities for organized criminal groups? (6) What services are used by organized criminal groups to implement their activities? Variables include information on the offense actually charged against the criminal organization in the indictments or complaints, other illegal activities participated in by the organization, and the judgments against the organization requested by law enforcement agencies. These judgments fall into several categories: monetary relief (such as payment of costs of investigation and recovery of stolen or misappropriated funds), equitable relief (such as placing the business in receivership or establishment of a victim fund), restraints on actions (such as prohibiting participation in labor union activities or further criminal involvement), and forfeitures (such as forfeiting assets in pension funds or bank accounts). Other variables include the organization's participation in business-type activities--both illegal and legal, the organization's purpose for providing legal goods and services, the objectives of the organization, the market for the illegal goods and services provided by the organization, the organization's assets, the business services it requires, how it financially provides for its members, the methods it uses to acquire ownership, indicators of its ownership, and the nature of its victims.